Characterisation of seed dormancy of 12 Chilean species of Nolana (Solanaceae) from the coastal Atacama Desert. Issue 1 (22nd March 2021) - Hepp, Josefina; Gómez, Miguel; León-Lobos, Pedro; Montenegro, Gloria; Vilalobos, Luis; Contreras, Samuel
Abstract: The genus Nolana (Solanaceae) comprises numerous species endemic to the coastal Atacama Desert of Chile and Peru of high ornamental potential and conservation value. The environments in which these species have evolved and are present today correspond to particular conditions in the midst of a hyper-arid habitat, so the study of their germination requirements and characterisation of seed dormancy becomes important in terms of conservation but also for ecological and evolutionary purposes. Different treatments were performed on mericarps of 12 species of Nolana : control (intact seeds imbibed in distilled water), scarification in funicular plug and distilled water and scarification in funicular plug and addition of GA3 (500 ppm); their permeability to water was also tested. It was determined that the species did not present physical dormancy, as had been previously reported, but rather physiological dormancy (PD). Germination results after treatments were not homogeneous among all 12 species, indicating differences in their dormancy levels. Also, the important role of the endosperm in the prevention of germination for the studied Nolana species was highlighted. Regarding the relationship between the level of PD (expressed as the percentage of germination for the most successful treatment) and the latitudinal distribution of the species or their phylogenetic closeness, it was determined that, for the studied species, their proximity in terms of clades was more relevant than their latitudinal distribution.